(untitled) (Olhar de Professor, 2022)
This research paper analyzes educational reforms implemented in Brazil in the last decade, namely the High School Reform and implementation of the National Curricular Common Core. Qualitative document analysis focused on the National Curricular Common Core document and the website “Novo Ensino Médio” (“New High School”) as sources. Extracts of websites belonging to the organizations “Escola Sem Partido” ("Nonpartisan School”) and “Todos Pela Educação” (“All For Education”), as well as journalistic pieces on the subject, were also scrutinized. It is argued that educational reforms and the resolution to adopt one unified curriculum are political strategies of imposing specific knowledge and understading under the justification of improving teaching, enhancing High School efficiency, and overall increasing of quality in education. Knowledge regarding gender is neglected under such curriculum, which aims to cast out any knowledge considered to be idological.